Theoretical modelling of the collaboration between consumers and providers of educational services in the implementation of school’s mission - Gumuliauskienė, Aušrinė; Starkutė, Jovita (Social Welfare: Interdisciplinary Approach, 2018)
The article deals with the problem of the collaboration between consumers and providers of educational services in the implementation of school’s mission. The concept of the consumers and providers of school services has been presented, the mission of the school of today has been defined, the contradictions of its implementation in the postmodern society have been highlighted, the importance of the collaboration between parents as consumers of educational services and pedagogues as providers of educational services in the implementation of school’s mission has been substantiated, the factors conditioning collaboration, the principles determining the involvement and participation of the consumers of educational services, and the essential elements of collaboration have been actualized. A theoretical interpretation of the concept of value creation in interaction has been presented. Referring to the analysis and meta-analysis of the development and structure of the collaboration process at school a theoretical model of the development of collaboration between consumers and providers of educational services at school has been conceptualized.
Keywords: consumers of educational services; providers of educational services; collaboration; school’s mission